The Role of Supply Chain Strategy and Affiliate Marketing in Increasing the Demand for E-Commerce – Social Media POV - Ehab Kamal Haikal; Sultan Mohammed Freihat; Diana Homsi; Jamal M. M. M. M. Joudeh; Tareq N. Hashem (International Journal of Supply Chain Management, 2020)
Abstract- The study examined the most influential affiliate marketing and supply chain strategies that are most beneficial and usable through social media websites which can increase the demand on e-commerce. Through employing the quantitative approach; the researchers distributed total of (95) questionnaires on marketing managers within cosmetics companies in Jordan- Amman during the fiscal year (2018-2019). Results of study indicated a high level of awareness and dependency of cosmetics companies on marketing through social media websites as a form of endorsement. In addition to that, it appeared that among the chosen affiliate marketing strategies CPC/PPC was the most influential and usable strategy through social media as a form of endorsement and marketing